An Alternative Stiffening Method for Rigid CHS L-Joints. (30th June 2016) - Holmes, Niall; Kierans, Darran; Crean, Patrick
Abstract : The paper presents a new method of stiffening CHS L-joints and compares it against current stiffened and unstiffened moment connections. The method is derived from studying the failure modes of existing methods, typically local buckling and ovalisation of the section. Unstiffened right-angled CHS connections have been shown to be weak due to local buckling and ovalisation. Stiffing plates placed across the joint can increase the moment capacity of the section by preventing ovalisation of the section but is architecturally unsightly. An alternative approach, where a stiffening plate welded vertically inside both the column and beam, outperformed the unstiffened frame plate in terms of reduced ovalisation and increased load capacity. It was also found to perform better than the stiffened connection in terms of both vertical and horizontal deflection. However, more research is required to ensure a fully restrained connection to satisfy codes of practice and constructible.